2010
DOI: 10.3892/or_00001070
|View full text |Cite
|
Sign up to set email alerts
|

A novel polysaccharide from Se-enriched Ganoderma lucidum induces apoptosis of human breast cancer cells

Abstract: Abstract. The novel polysaccharide SeGLP-2B-1 isolated from Se-enriched Ganoderma lucidum, showed antiproliferative activity towards several cancer cell lines in vitro. To investigate the antitumor mechanisms, the apoptotic effects of SeGLP-2B-1 in human breast cancer cells were studied, and the mechanism of this action was further elucidated. Cell apoptosis was detected by Annexin V/PI staining. Caspase activity was assayed using a caspase apoptosis detection kit. Western blot analysis was used to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 19 publications
4
55
0
Order By: Relevance
“…As previously demonstrated, uptake of elements such as Se by G. lucidum can weaken the antitumor and immunomodulatory effects of its polysaccharides and proteins [34,35]. As demonstrated in the present study, the Se was detected only in some fruiting bodies with the highest mean contents identified for cultivated G. capense (1.37 mg kg −1 ) and G. lucidum (1.41 mg kg −1 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As previously demonstrated, uptake of elements such as Se by G. lucidum can weaken the antitumor and immunomodulatory effects of its polysaccharides and proteins [34,35]. As demonstrated in the present study, the Se was detected only in some fruiting bodies with the highest mean contents identified for cultivated G. capense (1.37 mg kg −1 ) and G. lucidum (1.41 mg kg −1 ).…”
Section: Discussionsupporting
confidence: 78%
“…It should be highlighted that Al is poorly absorbed in the gastrointestinal tract (usually 0.1-1.0% of an oral dose) and in healthy subjects almost the entire amount of absorbed Al is excreted readily from the body [47]. Increased accumulation in humans, predominantly in the brain, occurs in patients suffering renal failure or if doses exceed excretory capacity [34], and has been implicated in neurodegenerative processes [48]. The provisional tolerable weekly intake (PTWI) for Al is 2 mg kg −1 body weight [49].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been described as one of the more important mechanisms for the anticancer action of selenium-based compounds. [35][36][37] Although Valdiglesias et al 38 reported that the induction of apoptosis by Seleniumbased compounds may be related to changes in the cell cycle, Suchocki et al 20 found that free selol did not overset the cell cycle in human leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that GLP can mediate cytotoxicity in number of cancer cell lines including lung cancer, prostate cancer and breast cancer. Further studies showed that GLP programmed cell death through endothelial growth factor overexpression and tumor angiogenesis inhibition in highly metastatic mouse melanoma B16F10 cells (Sun et al, 2011), through endotoxin-induced intercellular cell adhesion molecule-1 (ICAM-1) upregulation in the neointima in mice (Liu et al, 2010), through cell differentiation and p53 activation in human monocytic leukemia THP-1 cells (Hsu et al, 2011), through activation of mitochondrial signaling pathway in MCF-7 breast cancer cells (Shang et al, 2011). GLP can also boost anticancer immunity by changing lymphocyte phenotype in H22 hepatoma mice (Zhou et al, 2009), by enhancing CD56 + NK-cell cytotoxicity in cord blood (Chien et al, 2004), by promoting the proliferation of B cells in mice (Jiang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%